Hubungan Antara Penerimaan Kelompok Teman Sebaya dengan Prestasi Akademik Mahasiswa Pada Fakultas Ekonomi Universitas Negeri Jakarta - Sumiyati, Ati; Chairunnissa, - (Jurnal Ekonomi dan Pendidikan, 2012)
This research was purposed to obtain valid and reliable data about whether the peer group acceptance correlation with academic achievement. Data were collected using a survey on 78 students of Accounting Education Student at Faculty of Economics, Universitas Negeri Jakarta with a sampling technique using propotionate random sampling. The survey was conducted by distributing questionnaires to the samples who have determined. Scores of self – report peer group acceptance report obtained by giving questionnaires with Likert type scale. While the academic achievement is used to index the value of a Grade Point Average (GPA) students of the semester for about 5 semesters 089 – 093 during the academic year 2008 to 2011 of every subject. The regression equation in this research is Å¶ = 2.236 + 0.011X. From this equation, test requirements analysis conducted by the normality test error estimate the regression of Y on X obtained by test Liliefors Lo <Lt (0.0628 <0.1003). It mean the data are normally distributed. On the linearity The regression test we got the result Fh <Ft (1.28 < 1.84) which can be concluded that the regression model is linear. As for the meaningful test obtained Fh>Ft (23.58 > 4.00) which indicates that the regression equation is meaning. The test results by using the correlation coefficient of Pearson product moment values obtained rxy=0.494. This means there is a positive correlation between peer group acceptance with the academic achievement of students at Faculty of Economics, University of Jakarta. From the test calculations obtained thitung> ttable, is 4956>1.69 indicating a significant correlation between variable X that is peer group acceptance a variable Y that is academic achievement. From the results obtained by calculating the coefficient of determination 24.4% so it can be said that the academic achievement variable Y is determined by the variable X peer group acceptance of 24.4%.